Associations of sunlight affinity with depression and sleep disorders in American males: Evidence from NHANES 2009–2020 - Haifeng Liu; Jia Yang; Tiejun Liu; Weimin Zhao (PLoS ONE, 2025)
Objective Depression and sleep disorders are globally prevalent, yet male-specific studies remain scarce. This study investigates associations between sunlight affinity (a novel dual-dimensional metric comprising psychological [sunlight preference score, SPS] and behavioral [sunlight exposure duration, SED] dimensions) and subthreshold depression (StD), major depressive disorder (MDD), short sleep, and trouble sleeping in American males. Methods We analyzed weighted data from 7,306 males in the National Health and Nutrition Examination Survey (2009–2020) and assessed sunlight affinity’s associations with depression and sleep disorders based on multiple logistic regression, threshold effects analysis, restricted cubic spline (RCS) analysis, subgroup analysis, and mediation analysis. Results Adjusted multiple logistic regression analyses showed SPS inversely associated with StD (OR = 0.88, 95% confidence interval [CI]: 0.80–0.96) and MDD (OR = 0.80, 95% CI: 0.69–0.92), but positively with short sleep (OR = 1.11, 95% CI: 1.04–1.19). SED negatively correlated with MDD (OR = 0.90, 95% CI: 0.84–0.96) and trouble sleeping (OR = 0.94, 95% CI: 0.90–0.98), while positively with short sleep (OR = 1.05, 95% CI: 1.01–1.10). The highest SED quartile had reduced StD risk (OR = 0.70, 95% CI: 0.52–0.94). RCS analysis revealed a U-shaped relationship between SPS and short sleep (P-nonlinearity = 0.003). Threshold analyses identified SPS inflection points: ≥ 2.867 linked to higher short sleep risk (OR=1.17, 95% CI: 1.08–1.26) and ≥4 to lower trouble sleeping (OR=0.62, 95% CI: 0.48–0.80). Subgroup analyses revealed significant interactions across different populations. Mediation analysis suggested potential suppression effect of sunlight affinity in the bidirectional cycles between depression and sleep disorders. Conclusion This study revealed that sunlight affinity was inversely associated with depression and trouble sleeping and positively associated with short sleep in males. Further longitudinal studies are needed to confirm causality.